Multidisciplinary Treatment of Pediatric Low-Grade Glioma: Experience of Children Cancer Hospital of Egypt; 2007-2012 - Fawzy, Mohamed Ahmed; El-Hemaly, Ahmed Ibrahim; Awad, Madeeha; El-Beltagy, Mohamed; Zaghloul, Mohamed Saad; Taha, Hala; Rifaat, Amal; Mosaab, Amal (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: Pediatric gliomas comprise a clinically, histologically, and molecularly heterogeneous group of central nervous system tumors. The survival of children with gliomas influenced by histologic subtype, age, and extent of resection. Tumor grade emerged as the most determinant of survival except in the young age groups. The aim of this study was to evaluate the role of multidisciplinary therapeutic approach including surgery and chemotherapy, and their impact on the outcome in pediatric patients with low-grade glioma (LGG). Procedure: Study patients were prospectively enrolled onto the study. All patients were below 18-year-old, diagnosed as LGG between July 2007 and June 2012. Upfront surgical resection was attempted in all tumors other than optic pathway sites. Systemic chemotherapy was given according to CCG-A9952 protocol. Results: Total/near-total resection in 105/227 (46.3%) without adjuvant treatment, while 49/227 patients (21.5%) underwent subtotal tumor resection followed by chemotherapy for big residual (n = 26). Follow-up only was indicated for asymptomatic/small residual (n = 23). The radiological diagnosis was set in 18/227 (7.9%) patients; 13/18 had optic pathway glioma. The 3-year overall survival (OS) was 87.3% versus 65.5% event free survival (EFS) for the whole study patients with a follow-up period of 1–5 years. The OS and EFS for patients who did surgery with no adjuvant treatment (n = 128) were, respectively, 95.2% and 77.3% versus 87.4% and 65.1% for adjuvant chemotherapy group (n = 99); (P = 0.015 and P = 0.016 for OS and EFS, respectively). Conclusion: Pediatric LGGs comprise a wide spectrum of pathological and anatomical entities that carry a high rate of prolonged survival among children and adolescents. Surgical resection is the mainstay of treatment in most of tumors. Combined chemotherapy can be an acceptable alternative when surgery is not safely feasible.
Keywords: Chemotherapy; low-grade glioma; outcome; pediatric